2009
DOI: 10.1371/journal.ppat.1000431
|View full text |Cite
|
Sign up to set email alerts
|

B7-H1 Blockade Increases Survival of Dysfunctional CD8+ T Cells and Confers Protection against Leishmania donovani Infections

Abstract: Experimental visceral leishmaniasis (VL) represents an exquisite model to study CD8+ T cell responses in a context of chronic inflammation and antigen persistence, since it is characterized by chronic infection in the spleen and CD8+ T cells are required for the development of protective immunity. However, antigen-specific CD8+ T cell responses in VL have so far not been studied, due to the absence of any defined Leishmania-specific CD8+ T cell epitopes. In this study, transgenic Leishmania donovani parasites … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
178
2
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 140 publications
(193 citation statements)
references
References 74 publications
11
178
2
2
Order By: Relevance
“…We have previously shown that L. donovani induces defective CD8 T cell responses with limited expansion capacity (23). Interestingly, although most of the CD8 T cells during peak expansion are CD62L lo , they do not express other markers typically associated with effector cells, such as PD-1 (23), Fas (data not shown), or KLRG1, and the majority of the CD62L lo effectors are uncharacteristically highly positive for Bcl2 (data not shown).…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations
“…We have previously shown that L. donovani induces defective CD8 T cell responses with limited expansion capacity (23). Interestingly, although most of the CD8 T cells during peak expansion are CD62L lo , they do not express other markers typically associated with effector cells, such as PD-1 (23), Fas (data not shown), or KLRG1, and the majority of the CD62L lo effectors are uncharacteristically highly positive for Bcl2 (data not shown).…”
Section: Discussionmentioning
confidence: 87%
“…All Abs unless specified were from BD Pharmingen. For intracellular staining, splenocytes were stimulated with the SIINFEKL peptide (Genosphere Biotechnologies) and IL-2 (Amgen) in the presence of brefeldin A (BD Pharmingen) for 4 h at 37˚C followed by surface staining for anti-CD45.2/1 and -CD8 (23). The cells were then fixed, permeabilized, and stained with either isotypes or anti-granzyme B-PE (Caltag), anti-IFN-gallophycocyanin, anti-IL-2-PE (BD Pharmingen), and anti-TNF-a-PECy7 (eBioscience).…”
Section: Flow Cytometrymentioning
confidence: 99%
See 2 more Smart Citations
“…Cytokine secretion can be limited by the T cell exhaustion state 12, 32 during chronic viral infections 33, 34, malignant tumors 35, and parasitic diseases 36. Chronic chagasic patients displayed dysfunctional T cell responses characterized by increased frequency of terminally differentiated cells, monofunctional antigen‐specific T cell responses and progressive attenuation of cytokine production 7, 10, 21, 37.…”
Section: Discussionmentioning
confidence: 99%